How to Compute the Economic Impact of a Sudden Stop of Gas Imports from Russia - Tom Krebs (Wirtschaftsdienst)
Abstract In this essay, I outline a method to compute the economic impact of a sudden stop of natural gas imports from Russia. First, I estimate the reduction in the short-run supply of natural gas for the economy and the industry sector. Second, I use model simulations to analyse the effect of a sudden import stop on the industry sectors using natural gas and the whole economy. The model should take into account the limited short-run substitution possibilities of the industry sectors using natural gas (chemical industry) and the value chain linkages of these sectors with all other sectors of the economy. The recent analysis by Bachmann et al. (2022) does not satisfy these two methodological conditions and the results should be interpreted accordingly.